Description of hydrocephalus knowledge in pregnant woman at Puskesmas 1 Denpasar Utara - Made Indra Erlangga Prathiwindya; I Wayan Niryana; Tjokorda Gde Bagus Mahadewa; Sri Maliawan (DiscoverSys Inc., 2022)
Background: Hydrocephalus is a pathological brain disorder resulting from increased cerebrospinal fluid without or with elevated intracranial pressure resulting in widening of the space where cerebrospinal fluid flows. Maternal environment such as experiencing infection during pregnancy, consuming alcohol and drugs, lifestyle such as obesity, diabetes, or hypertension, and lack of examinations in preparing for prenatal care and low socioeconomic status affect the risk factors for congenital hydrocephalus. The purpose of this study is to to determine awareness and knowledge level among pregnant women towards hydrocephalus. Methods: This descriptive research was conducted with a cross-sectional method using consecutive sampling as a sampling technique. 106 Pregnant Women at Puskesmas I Denpasar Utara was involved in completing the survey regarding Hydrocephalus during this research. For the collecting data using a questionnaire filled directly by each respondent containing 9 questions and then analyzed using the software Statistical Package for the Social Sciences (SPSS). Results: This study was participated by 106 respondents and figured that approximately 84,9% among the total number of respondents have a good knowledge of hydrocephalus while the rest, 15,1% are still at a low level with common characteristics of the respondents, including the age of 24 years old (age group 19-25), multipara (59.4%), with a college education background (45.3%), and working as a housewife (59.4%). Conclusion: This study conveys good knowledge about hydrocephalus in pregnant women, especially those who have a good level of education.